Four-legged hunter (FLH) robot: design and shooting control to moving targets with SMC - Tatar, Ahmet Burak; Tanyildizi, Alper Kadir; Yakut, Oguz (Elsevier, 2020)
The design and control of robotic shooting control systems in defense systems is one of the important research topics in recent years. This study focuses on the design, modeling, and success of the shooting control system of the 14 Degrees of Freedom (DoF) Four Legged Hunter Robot (FLH) system with 2 DoFs gun barrel systems. The three-dimensional dynamic model of the FLH-Robot with gun barrel system was created by the Simscape Multibody toolbox of the MATLAB program. The leg joints of FLH were controlled by the PID control method to perform the motion of the robot. Gun barrel stabilization was performed in order to ensure the orientation of the gun barrel system to the predetermined targets and to enhance the hitting success rate. Mechanical oscillations in the robot body were applied as a disruptive effect on the gun barrel system. The sliding-mode control (SMC) method was applied to 2 DOFs gun barrel system. Ballistic simulations were repeated for situations where the targets were fixed and mobile. While the robot was walking, in the first shooting scenario, the shots made on fixed targets placed in random coordinates were hit with a maximum error of 3.3 cm. In the second shooting scenario, shots were fired on moving targets at a speed of 0.1 to 1 rad / s, and hitting success was achieved with a maximum error of 0.387 m. When hit error rates are analyzed, the usability of FLH-Robot for the defense industry was demonstrated.
Keywords: FLH-Robot; Simscape multibody model; Walking Pattern; Sliding mode control; Gun turret